Can Landscape Composition Predict Movement Patterns and Site Occupancy by Blanding's Turtles?: A Multiple Scale Study in Québec, Canada - Fortin, Gabrielle (Université d'Ottawa / University of Ottawa, 2012)
As habitat loss and fragmentation are major causes of decline in animal species, studying habitat requirements in these species is a key component of their recovery. I investigated the relationship between landscape composition and habitat use of Blanding’s turtles, Emydoidea blandingii, a freshwater turtle threatened by habitat loss and road mortality on most of its Canadian range. In 2010, I conducted a radio-telemetry survey of 44 Blanding’s turtles in southern Québec, Canada, and modelled their home range size from land cover proportions measured at many spatial scales. I also used data from a visual survey conducted in 2008 and 2009 to model wetland occupancy of the species at the landscape scale. Home range size of the Blanding’s turtle was significantly correlated to landscape composition, and the proportions of agriculture, open water and anthropogenic lands had the strongest relationships with home range size. However, those relationships were weak and the models were unable to predict home range size accurately. At the landscape scale, land cover and road density poorly predicted probability of occurrence, and Blanding’s turtles occupied wetlands in both disturbed and natural sites. Management of the species should focus on protecting sites of occurrence with high wetland density, low road density, and sufficient suitable habitat to cover their seasonal movement patterns.
Keywords: Emydoidea blandingii; Landscape composition; Home range size; Wetland occupancy; Habitat use; Modelling; Conservation